Generation of a femtosecond vacuum ultraviolet optical pulse by four-wave Raman mixing. (February 2017) - Vu, Duong; Nguyen, Trong Nghia; Imasaka, Totaro
Highlights: Three color Four Wave Raman Mixing generating at vacuum ultraviolet is investigated. The revivals of molecular vibration can help to improve the conversion efficiency. A conversion efficiency from the probe to the first anti-Stokes was achieved at 16%.